Positions of early nonsense and deletion mutations in lacZ. - Welply, J K (1980)
The positions of three Escherichia coli lacZ operator-proximal nonsense mutations and one deletion mutation have been determined. The nonsense mutations were suppressed with supF, resulting in the production of active beta-galactosidase by each strain. Amino acid sequencing identified the positions of the tyrosine residues inserted by supF, and thereby established that nonsense mutations lacZ2, lacZ2246, and lacZU131 are at sites corresponding to amino acids 23, 36, and 41 of beta-galactosidase, respectively. The deletion mutant, lacZM112, produced a dimeric beta-galactosidase protein missing amino acid residues 23 through 31 of the native enzyme.